The reporting of adverse drug reactions by healthcare providers in Kenya - David Muriithi Nyagah; Daniel Mokaya; Simon Muturi Karanja (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2020)
Background: Spontaneous and consistent reporting is the cornerstone of adverse drug reaction (ADR) reporting. Under reporting is an enormous obstacle to effective pharmacovigilance (PV). Objective: To determine factors affecting ADR reporting by healthcare providers in selected hospitals in Kirinyaga County, Kenya. Methods: A cross-sectional study was conducted in four selected hospitals. A pretested self-administered questionnaire was utilised to collect data. Stratified sampling was used to recruit 224 healthcare providers. Statistical Package for Social Sciences (SPSS) version 23 analysed data. The Chi-squared test was used to determine association. Binary logistic regression assessed strength of association. Outcomes were considered significant at p-values of <0.05. Results: Of 224 questionnaires distributed 215 were completed, 159 (74%) healthcare providers had not reported ADRs to the Pharmacy and Poisons Board (PPB) within the last 3 months. In total, 92 (42.8%) healthcare providers knew about reporting guidelines; 194 (90.2%) were not trained in ADR reporting. Those aware of the reporting guidelines and those trained were more likely to report ADRs. Continuing medical education was the preferred source of information about ADRs. The main barriers to ADR reporting include inadequate training, delayed feedback, not knowing where or to whom to report, lack of a PV centre in the county and inadequate access to ADR forms and guidelines. Conclusion: ADR reporting among healthcare providers could be improved. Age, profession, level of education, knowledge and training affected ADR reporting. Healthcare provider centred training and promotion of ADR reporting tools are necessary to boost ADR reporting and increase patient safety.